Parallel Synthesis and Biological Screening of Dopamine Receptor Ligands Taking Advantage of a Click Chemistry Based BAL Linker - Löber, Stefan; Gmeiner, Peter; Hübner, Harald; et al. (Journal of Combinatorial Chemistry, 2005)
The click-chemistry-derived formyl indolyl methyl triazole (FIMT) resin 1a was evaluated for the parallel solid-phase synthesis of a series of BP-897-type arylcarboxamides. By application of a five-step sequence (including loading by reductive amination, subsequent amide coupling, deprotection, palladium-catalyzed N-arylation, and acidic cleavage), a focused library of putative dopamine D3 receptor ligands was constructed. The final products revealed good to excellent purity and were screened for binding at monoaminergic G-protein-coupled receptors when selected library members proved to show excellent binding affinity, especially toward the dopamine D3 receptor subtype. © 2005 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.lphch.parall